The Acta Pekinensia or Historical Records of the Maillard de Tournon Legation: First transcribed edition and English annotated translation - Danieluk, Robert (Annales Missiologici Posnanienses, 2023)
Recenzja książki: Kilian Stumpf, The Acta Pekinensia or Historical Records of the Maillard de Tournon Legation: First transcribed edition and English annotated translation. Vol. I: December 1705 – August 1706. Editors Paul Rule, Claudia von Collani. Rome, Institutum Historicum Societatis Iesu; Macau, Macau Ricci Institute, 2015 (Monumenta Historica Societatis Iesu. Nova Series 9).